The species of Campodorus Förster, 1869 and a related species (Hymenoptera, Ichneumonidae) from China - Sun, Shu-Ping; Li, Tao; Sheng, Mao-Ling; Lü, Jun (European Journal of Taxonomy, 2020)
Ten species of Campodorus Förster, 1869 are reported from China and five species are new to science: C. albilineatus Sheng, Sun & Li sp. nov. from Guangxi Zhuang Autonomous Region in the Oriental part of China, C. punctatus Sheng, Sun & Li sp. nov. and C. rasilis Sheng, Sun & Li sp. nov. from Beijing, C. shandongicus Sheng, Sun & Li sp. nov. from Shandong Province and C. truncatus Sheng, Sun & Li, sp. nov. from Liaoning Province. Three species, C. ciliatus (Holmgren, 1857) and C. dauricus Kasparyan, 2005 collected from Liaoning Province and Mesoleius faciator Kasparyan, 2001 from Beijing, are new records for China. A key to species of Campodorus and a related genus known in China is provided.